The Gambian 2016 Presidential Election and its Aftermath. Issue 3 (4th May 2017) - Perfect, David
Abstract: This article explores the Gambian presidential election of December 2016, which was very surprisingly won by the leader of an opposition coalition, Adama Barrow, and its extraordinary aftermath. Barrow defeated Yahya Jammeh, who had won the four previous presidential elections, thus ending Jammeh's 20-year rule of The Gambia, which had been marred by human rights abuses. Jammeh at first accepted the result, but changed his mind a week later, thus triggering a major political crisis. Over the next month, he made various desperate attempts to cling to power, before finally leaving the country on 21 January 2017, when faced with the prospect of being removed by force. Barrow, who had earlier been inaugurated as president, finally returned to Banjul on 26 January to assume office. The article concludes by considering the possible key features of a Barrow presidency and assesses the challenges that he will face.